1998
DOI: 10.1136/oem.55.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biological and analytical variation on urine measurements for monitoring exposure to cadmium.

Abstract: Objective-To define the mean intraindividual biological variation in urinary concentrations of cadmium and retinol binding protein (RBP) in untimed, random urine samples and the influence of creatinine or specific gravity correction on reducing this variation. The relation between biological variation and analytical variation in defining uncertainty in a single measurement and significant differences between successive measurements was explored. Methods-Repeat measurement study in subjects with either high his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Although it has been a common practice in Cd epidemiology (World Health Organization 1996; American Conference of Governmental Industrial Hygienists 2003) to correct urinary analyte concentration by CR concentration; Berlin et al (1985), for example, did not find any advantage of CR correction over the use of observed values, although Mason et al (1998) observed that CR correction might reduce intra-individual variation when multiple samples were collected from the same individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Although it has been a common practice in Cd epidemiology (World Health Organization 1996; American Conference of Governmental Industrial Hygienists 2003) to correct urinary analyte concentration by CR concentration; Berlin et al (1985), for example, did not find any advantage of CR correction over the use of observed values, although Mason et al (1998) observed that CR correction might reduce intra-individual variation when multiple samples were collected from the same individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, biological variation of urinary Cd as a Cd exposure marker, separately from possible analytical problems (such as instrument-dependent bias; Zhang et al 1997), has been calling attention of several researchers (Arisawa et al 1997;Mason et al 1998;Ikeda et al 2005). This study group also has reported wide variation in Cd-U (Yamagami et al 2006), assumedly due to seasonal changes in types of foods consumed (Kruzynski 2004;Bragigand et al 2004).…”
Section: Introductionmentioning
confidence: 90%
“…During the physical examination, a 10-ml specimen of urine was collected as a "spot" or untimed sample in a container previously screened for cadmium. Studies of timed urine specimens indicate that urinary cadmium levels do not show significant diurnal variation [10] and that urinary cadmium in spot specimens correlates well with urinary cadmium levels in 12-and 24-h specimens [11]. Urinary cadmium was measured by Zeeman effect graphite furnace atomic absorption spectrometry [12] to adjust for variation in urine concentration.…”
Section: Measurementsmentioning
confidence: 99%